The spaces OM and OC are ultrabornological a new proof - Jan Kucera (International Journal of Mathematics and Mathematical Sciences)
In [1] Laurent Schwartz introduced the spaces 𝒪M and 𝒪′C of multiplication and convolution operators on temperate distributions. Then in [2] Alexandre Grothendieck used tensor products to prove that both 𝒪M and 𝒪′C are bornological. Our proof of this property is more constructive and based on duality.